“DEVELOPMENT OF A MARKETING STRATEGY USING THE EXAMPLE OF A CONFECTIONERY FACTORY” (Journal of Science-Innovative Research in Uzbekistan, 2023)
Enterprise strategy is the development of marketing strategies. The development of marketing strategies is considered as a key stage in the strategic planning process of the enterprise as a whole and is a necessary element to achieve the best results of the company's activities